Pengaruh Corporate Governance terhadap Tax Avoidance (Studi Empiris Perusahaan Sektor Energy Terdaftar di Bursa Efek Indonesia Tahun 2021-2023 - Mazro 'atul Ulya Ahmad; Imam Setijawan (Jurnal Ilmiah Raflesia Akuntansi, 2026)
This study aims to analyze the effect of Corporate Governance, measured by Institutional Ownership, Independent Commissioners, Audit Quality, and Audit Committees, on Tax Avoidance in energy sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2021-2023. This study uses a quantitative approach with research data obtained from secondary data in the form of financial statements and annual reports. The sampling technique used purposive sampling, resulting in 89 samples from 34 companies. The data analysis technique in this study used multiple linear regression analysis processed using SPSS software version 26. The results of this study show that Institutional Ownership, Independent Commissioners, Audit Quality, and Audit Committees simultaneously have a significant effect on Tax Avoidance. However, partially, Institutional Ownership has a negative effect on Tax Avoidance, Independent Commissioners do not have a negative effect on Tax Avoidance, while Audit Quality and Audit Committees do not have a positive effect on Tax Avoidance. These findings confirm that corporate governance is important in tax avoidance practices, but not all components are effective in reducing tax avoidance actions. This study is based on agency theory, which explains the supervisory role of corporate governance in minimizing tax avoidance in companies.